Prospective associations between internalising symptoms in youth and educational achievement: A monozygotic twin differences study - Leigh, E; Rimfeld, K; Bowes, L; Clark, D; Eley, T; Krebs, G (Elsevier, 2022)
Background: Educational achievement is an independent predictor of many life outcomes and so it is important to understand its causes and correlates. Internalising symptoms, encompassing anxiety and depression symptoms, are one candidate influence. Methods: Using a prospective and genetically-informative design, the present study investigated the associations between internalising symptoms and educational achievement, controlling for IQ at age 7 years and socioeconomic status, among participants of the Twin and Early Development Study (up to N = 10,791). Internalising symptoms were measured by the parent-rated Anxiety Related Behaviours Questionnaire (ages 7, 9, 16 years), and educational attainment were indexed by UK-wide standardized examination results at ages 16 and 18 years, and self-reported transition to university education. Results: Negative affect was the only internalising symptom subtype that was uniquely associated with academic underachievement at all timepoints, from mid-adolescence to early adulthood. The association between negative affect and achievement became non-significant when using MZ twin difference scores, suggesting that the majority of the relationship is accounted for by genetic and shared environmental effects. Limitations: Limitations include the reliance on parent-reported internalising symptoms. Conclusions: Negative affect in youth may be an important marker of later academic underachievement. Findings suggest that academic underachievement is not simply a consequence of the disruption caused by negative affect symptoms and therefore educational interventions may be required to optimise outcomes.